2019
DOI: 10.1161/hypertensionaha.118.11873
|View full text |Cite
|
Sign up to set email alerts
|

MR (Mineralocorticoid Receptor) Induces Adipose Tissue Senescence and Mitochondrial Dysfunction Leading to Vascular Dysfunction in Obesity

Abstract: Adipose tissue (AT) senescence and mitochondrial dysfunction are associated with obesity. Studies in obese patients and animals demonstrate that the MR (mineralocorticoid receptor) contributes to obesity-associated cardiovascular complications through its specific role in AT. However, underlying mechanisms remain unclear. This study aims to elucidate whether MR regulates mitochondrial function in obesity, resulting in AT premature aging and vascular dysfunction. Obese (db/db) and lean (db/+) mice were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 54 publications
2
26
0
2
Order By: Relevance
“…Recently, it was observed that adipose tissue senescence, via mineralocorticoid receptor activation, contributed to increased arterial contractile responses. 74 This illustrates that senescent PVAT can mediate premature vascular aging by promoting hypercontractility.…”
Section: Perivascular Adipose Tissuementioning
confidence: 97%
“…Recently, it was observed that adipose tissue senescence, via mineralocorticoid receptor activation, contributed to increased arterial contractile responses. 74 This illustrates that senescent PVAT can mediate premature vascular aging by promoting hypercontractility.…”
Section: Perivascular Adipose Tissuementioning
confidence: 97%
“…Also, the deletion of PGC-1α (proliferator-activated receptor-gamma and coactivator 1 alpha) in aged PVASCs exacerbates arterial remodeling and attenuates the browning of adipose tissue [82]. A recent study has revealed that the mineralocorticoid receptor (MR) is activated in the mitochondria of PVAT in obese mice, which causes premature-aging in adipose tissue and senescence, resulting in the loss of the anticontractile effects [83]. These results suggest that downregulation of PGC-1α and mitochondrial dysfunction in PVAT may contribute to the aging phenotype.…”
Section: Aging and Pvat Dysfunctionmentioning
confidence: 99%
“…To date, few studies have investigated PVAT senescence, and both aging and obesity might affect PVAT in a comparable manner (Miao and Li, 2012). A recent report shows that mineralocorticoid receptor (MR) is activated in the mitochondria of PVAT which causes premature-aging in adipose tissue and senescence in obese mice model, resulting in the loss of PVAT anticontractile properties (Lefranc et al, 2019). This suggests that mitochondrial dysfunction in PVAT may contribute to the aging phenotype, which is worth further investigation.…”
Section: Sirt1 and Vascular Agingmentioning
confidence: 99%